Application of plants as eco-friendly components against common bed bugs (Cimex lectularius L.): a systematic review of the literature. Issue 3 (4th May 2023) - Aghaei Afshar, Abbas; Sharififard, Mona; Jahanifard, Elham; Gorouhi, Mohammad Amin; Yousefi, Saideh; Shirani-Bidabadi, Leila; Faraji, Maryam; Alizadeh, Ismaeil
ABSTRACT: The objective of this study was to review the studies used plants and plant components against Cimex lectularius. Standard procedure for systematic reviews was followed. Various electronic databases were investigated for choosing reliable researches from 1990 to 2021. In total, 18 papers were selected among the 300 papers. Totally, 26 plants were evaluated in the published studies. Plants included Thymus vulgaris, Origanum vulgare, Mentha piperita, Syzygium aromaticum, and plant components of Thymol, Carvacrol and Linalool have the highest frequency in the papers studied. Maximum mortality and repellency of up to 100% were reported for the essential oils of Tagetes patula, Schinus molle, and plants of Cinnamomum sp. Cymbopogon martinii, Mentha piperita, Salvia rosmarinus, Thymus vulgaris, Origanum vulgare, Nepeta cataria. The results of this review can provide a better understanding of the potential of extracts and essential oils made from these plants and plant components for researchers to control bed bugs.